1996
DOI: 10.1111/j.1365-2044.1996.tb07799.x
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic effects of propofol in combination with ephedrine

Abstract: SummaryForty ASA 1 patients presenting for minor gynaecological surgery were randomly allocated into four study groups to compare the haemodynamic effects of adding diyerent doses of ephedrine to an induction dose of propofol. Heart rate, oxygen saturation and non-invasive arterial blood pressure were monitored before and for Smin after induction. In those patients who received propofol alone, there was a significant decrease in both systolic (p < 0.001) and diastolic (p = 0.003) blood pressure. The addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 14 publications
6
29
0
4
Order By: Relevance
“…There was an increase in the heart rate at twenty minutes after induction. These results are in consistent with other studies in the literature 15,16 . However, there are some contradictory reports as well 17,18 .…”
Section: Discussionsupporting
confidence: 94%
“…There was an increase in the heart rate at twenty minutes after induction. These results are in consistent with other studies in the literature 15,16 . However, there are some contradictory reports as well 17,18 .…”
Section: Discussionsupporting
confidence: 94%
“…The control group had a hypotension incidence of 67.5%, while the ephedrine group that received 0.2 mg/kg showed 22.5% hypotension. Similar attenuation or complete prevention of hypotension were reported in eight other studies using ephedrine 0.1 mg/kg or 10-20 mg boluses [8][9][10]12,15,16]. El Tahan [6] also found that ephedrine improves ventricular contractility without causing relevant changes of left ventricular afterload.…”
Section: Propofol and Ephedrine Bolussupporting
confidence: 71%
“…Dosing of ephedrine varied from single bolus dosing to weight based dosing ranging from 10-15 mg to 0.07-0.2 mg/kg [6,[8][9][10][11][12][13][14][15][16]. Most trials had a timeframe for recording vitals ranging from 4-6 minutes with all trials showing similar results in this time frame.…”
Section: Propofol and Ephedrine Bolusmentioning
confidence: 99%
“…Our data was consistent with Michelsen et al 1 study where induction of anesthesia with propofol was followed by a decrease in heart rate. In contrast, Gamlin et al 2 found no effect of propofol on heart rate, whereas Turner et al 4 found increase in heart rate. These confl icting results can be explained by the different methods of anesthesia maintenance performed in these studies.…”
Section: Discussionmentioning
confidence: 92%
“…Anesthesiologists have attempted different methods to prevent the hypotensive effect of propofol during GA induction, including administration of fl uids and prophylactic use of medications with vasoconstriction activity [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%